EVALUASI PELAKSANAAN DIKLAT KEHUMASAN DI BALAI DIKLAT KEAGAMAAN DENPASAR TAHUN 2019 - I Wayan Arya Adnyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The role of public relations in this globalization era is very important, because it is thefrontline in information as a connecting bridge that is expected to bridge between the interestsof the government on the one hand, and the public on the other, so that the principle of publicrelations communication, namely two-way communication can be truely applied. The purposeof this study was to determine the reaction of Diklat participants to aspects of the curriculum,facilities, services and learning in the implementation of the Public Relations Training, at theDenpasar Religious Training Center. This research is a quantitative descriptive research withsurvey method. There are several evaluation models, but the one used in this study is theKirkpatrick model which consists of four levels, namely reaction, learning, behavior and impact.With limited research time, this study is only limited to the evaluation of level 1 and 2. Thereaction of the training participants to the curriculum aspects of the implementation of thePublic Relations Training in the very good category with an average score of 91.17. The reactionof Diklat participants to the aspect of facilities in the category was very good with an average of91.69. The reaction of Diklat participants to service aspects in the category was very good withan average value of 93.89. The training of participants in the training aspect of attitude in thecategory is very good with an average of 92.83, the aspect of knowledge in the category is goodwith an average of 83.42 and on the aspect of skills with a very good category with an averageof 94.57. To increase the reaction of Diklat participants in the implementation of diklat can bedone by increasing the frequency of extracurricular activities, arranging menus more varied.The learning of the training participants can be further improved by using effective and funmethods.